Barriers to Implementation Sustainable Cement Manufacturing in Kuwait - AlSanad, Shaikha (European Journal of Sustainable Development, 2018)
The concept of the sustainability has progressively become vital to business practice and research over the past decades because of rapid depletion of corporate social responsibility and disquiets over affluence inequality and natural resources. Cement, which is the key element of concrete, considered, as is the most, consumed material after water and this industry revealed one of the as most controversial industries due to its significant environmental impacts The cement industries are facing challenges to implement sustainable manufacturing into their products and processes. Thus, it is vital to evaluate the sustainable manufacturing in the cement industry. This paper is part of ongoing research aimed to identify and assess the extent of the utilization of efficient practice in the process of cement production in Kuwait and in turn produce new practice guidelines. Thus, the paper intends to address the challenge and barriers the sustainable manufacturing supposed to be suitable to the cement industry from the perspectives of the stakeholders. Consequently, research data was collected through a semi structure questionnaire survey of randomly selected professionals in cement factory in Kuwait. The results demonstration that vital barriers to sustainable cement factory such as Lack of environmental awareness by the industry, political decision makers, and clients , lack of strategy to promote sustainable construction, Inadequate regulation support , and Shortage of local environmental regulations Keywords: cement industry, sustainability, sustainable manufacturing, sustainable development